Restoration of phosphate mined lands: literature review with insights from Morocco - Bourazza, Anass; Hassane Sidikou, Abdel Aziz; Fenta, Berhanu Amsalu; Hirich, Abdelaziz (Frontiers in Environmental Science, 2025)
Phosphate mining is essential for global agriculture but poses significant environmental challenges, particularly in landscape degradation. This study reviews the current state and trends of phosphate mining, highlighting economic importance, environmental impacts, and sustainability issues. It evaluates restoration techniques, focusing on the effectiveness of various plant species in restoring mined areas. Key factors influencing successful rehabilitation include topsoil management, physico-chemical site characteristics, nutrient bioavailability, topography, and water availability. The study advocates for integrated land management strategies that combine tailored nutrient management plans, erosion control, and water conservation, particularly in arid climates. Strengthening and enforcing regulatory frameworks is crucial to ensure accountability in land rehabilitation, with a focus on sustainability. Recent legal advancements in Morocco aim to modernize mining operations and enhance environmental accountability. The findings recommend increased investment in research to develop innovative rehabilitation techniques and long-term monitoring programs to ensure adaptive management and continuous improvement of restoration outcomes.